Hollywood : the great stars [videorecording (DVD)] - Fonda, Henry, 1905-1982; Bacall, Lauren, 1924-2014; Astaire, Fred; Arliss, George, 1868-1946 (Dreamscape Media, LLC, 2020)
Hosted by Henry Fonda, this fascinating and informative documentary tracks the complex creation, development, and eventual demise of the Hollywood studio star system.